Epigenetic adaptations to environmental stress in aquatic species for conservation and aquaculture - Nurillaeva, Nargiza; Muhamed Abas, Hayder; Nazirbek, Azimjanov; Balasubramanian, Ramesh; Dewangan, Hemlata (International Journal of Aquatic Research and Environmental Studies, 2025)
Stress factors like variations in temperatures, salinity, hypoxia, and pollution are bad for the health and survival of aquatic life. Epigenetics has shown us that stress factors can leave lasting changes, such as DNA methylation, histone modifications, and non-coding RNA alterations, that do not equate to changes in the primary genetic sequence. Considering these changes helps in assessing the resilience of a species and broadening the survival options for the species in natural habitats as well as in aquaculture. The current research proposes an Epigenetic Stress Response Profiling (ESRP) approach, which combines methylation mapping in Whole-Genome Bisulfite Sequencing (WGBS), correlating the epigenome with RNA-Seq, and metabolomic fingerprinting to derive multi-omics whereby an individual is exposed to an environment and other factors are aberrated, and the individual responds adaptively. The ESRP approach uses model organisms, Oreochromis niloticus and Cyprinus carpio, exposed to thermal, hypoxic, and salinity stress. The acquired epigenomic signatures are interpreted through machine learning algorithms to determine candidate biosignatures correlated with/impacting stress and stress-related growth. The study outlines candidate stress-responsive gene networks and methylation hotspots that are actionable targets for stress tolerance and growth in selective breeding and conservation efforts. The integration of epigenetics with the management of aquaculture will aim to increase adaptive capacity, which will boost conservation of biodiversity and sustain fisheries. This will also aid in the conservation of biodiversity in aquaculture and fisheries in the face of changing environmental conditions.